The role of gut microbiota in different murine models of systemic lupus erythematosus - Ran Lu; Xin M. Luo (Taylor & Francis Group, 2024)
Systemic lupus erythematosus (SLE) is an autoimmune disorder characterized by immune system dysfunction that can lead to serious health issues and mortality. Recent investigations highlight the role of gut microbiota alterations in modulating inflammation and disease severity in SLE. This review specifically summaries the variations in gut microbiota composition across various murine models of lupus. By focusing on these differences, we aim to elucidate the intricate relationship between gut microbiota dysbiosis and the development and progression of SLE in preclinical settings.